ANALISIS KINERJA KEUANGAN DAN KESEHATAN PADA KOPERASI SIMPAN PINJAM XYZ SYARIAH CABANG PASAR BARU BEKASI (METODE CAMEL) - Rika Rahmawati; Emmelia Tan (Jurnal Bina Akuntansi, 2023)
Analysis of financial performance on cooperative health is a regular activity to gauge the state of cooperative health. The goal of this research is to evaluate the financial performance and overall health of the XYZ Sharia Savings and Loans Cooperative Branch Pasar Baru Bekasi for the years 2019 to 2022. Documentation and observation approaches are used in this study to acquire data. Based on the regulation of the Minister of Cooperatives and Small and Medium Enterprises of the Republic of Indonesia Number: 07/Per/Dep.6/IV/2016, the financial performance and health level of the XYZ Syariah Savings and Loans Cooperative Branch Pasar Baru Bekasi are being examined. The findings revealed that the KSP XYZ Syariah Pasar Baru Bekasi Branch's soundness level assessment, which was done for the soundness level assessment of cooperatives in 2019â€“2022, did not yield the highest score possible in terms of capital/capital aspects, earning asset quality aspects (assets), management, efficiency, and liquidity aspects, and that the results can be said to have yielded the value of the predicate â€œUNDER SUPERVISIONâ€. With a final score between 2019 and 2022 of 51.75%, and a final score between 2022 and 55.25%.